Web-based event information and attendance management system / Muhammad Aminuddin Ahmat - Ahmat, Muhammad Aminuddin (2020)
Events and activities are one of the important elements in the education system at the university such as UiTM. Normally, information on events and activities will be posted on the notice board. They are also announced that information on the official university web portal but sometimes the information is not up to date and the notice not stand out because of too many other information on the university web portal. An event cannot be done without the presence of the participants. Therefore, attendance management of the event must be well managed in order to ensure the event run smoothly. In this modern age, there are still many universities that still use manual methods to manage the attendance of participants for event. This causes the event cannot be dealt with efficiently because the number of university students has increased every year. Therefore, in line with developments in technology, Web-based Event Information and Attendance Management system has been developed to help UiTM management to handle events and activities held in UiTM Perlis branch, Arau campus. In addition, the project is also to apply iterative framework model in order to draft a good system workflow.